1988
DOI: 10.1007/bf00146227
|View full text |Cite
|
Sign up to set email alerts
|

Dark envelope solitons of fast magnetosonic surface waves in solar flux tubes

Abstract: We have studied the modulational stability of a finite-amplitude fast sausage magnetosonic surface wave traveling along a thin magnetic slab in the solar photosphere (chromosphere). The equation governing the evolution of the fast-wave envelope modulated by a slow wave driven by the ponderomotive force proves to be the cubic nonlinear Schr6dinger equation which in photospheric conditions admits only dark envelope soliton solutions. The possibility of the existence of such solitary waves in the solar atmosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The formation of sausage solitons in magnetic tubes was first suggested by Roberts & Mangeney (1982). Since then, numerous papers have addressed the soliton formation problem (Merzljakov & Ruderman 1985, 1986; Roberts 1985, 1987; Sahyouni, Zheliazkov & Nenovski 1988; Ofman & Davila 1997; Zhugzhda & Nakariakov 1997; Nakariakov & Roberts 1999; Ballai, Thelen & Roberts 2003; Ruderman 2003; Erdélyi & Fedun 2006; Ryutova & Hagenaar 2007). Most of the studies consider a sausage soliton ( m = 0 mode in magnetic tubes), but no observational support for the theory has been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of sausage solitons in magnetic tubes was first suggested by Roberts & Mangeney (1982). Since then, numerous papers have addressed the soliton formation problem (Merzljakov & Ruderman 1985, 1986; Roberts 1985, 1987; Sahyouni, Zheliazkov & Nenovski 1988; Ofman & Davila 1997; Zhugzhda & Nakariakov 1997; Nakariakov & Roberts 1999; Ballai, Thelen & Roberts 2003; Ruderman 2003; Erdélyi & Fedun 2006; Ryutova & Hagenaar 2007). Most of the studies consider a sausage soliton ( m = 0 mode in magnetic tubes), but no observational support for the theory has been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear waves in the presence of strong dispersion may be subject to modulational instability of narrow-spectrum packets of magnetosonic waves, a process described in terms of the nonlinear Schrödinger equation (see e.g. Sahyouni et al 1988;Nakaryakov et al 1991;Zhelyazkov et al 1994). This effect may take place in the low-frequency (long-wavelength) range of the magnetosonicwave spectrum, when the dispersion arises from the inhomogeneity of the plasma in the transverse direction.…”
Section: Introductionmentioning
confidence: 99%
“…Dvoryakovskii et al (1979) obtained the equation for fast magnetosonic modes in a homogeneous plasma contained in a rigid planar waveguide. Sahyouni et al (1988) showed that fast magnetosonic surface waves in a magnetic slab are stable with respect to modulational instability in the large-wavenumber limit. Their consideration was based upon a derivation of the NSE taking into account the ponderomotive force.…”
Section: Introductionmentioning
confidence: 99%
“…Sakai and Sonneup [5] have derived model equations which describe the long dispersive Alfven wave driving sound wave. On the other hand the equation governing the evolution of ( 335) the fast wave envelope modulated by a slow wave driven by the ponderomotive force has been derived for a sausage wave travelling along magnetic photospheric slab with rigid walls by Sahyouni et al [6]. Model equations describing dispersive Alfven-magnetosonic waves interaction have been derived by Shukla et al [7].…”
Section: Introductionmentioning
confidence: 99%